THE IMPACT OF COVID-19 ON PRICES AND TRADING VOLUME OF STOCK IN TOURISM AND HOSPITALITY SECTOR ON SOUTHEAST ASIA STOCK MARKET - Nabilah, Putri; Maryasih, Lilis (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
COVID-19 is an unprecedented event that has devastated the world. Almost all sectors of the economy are impacted. Coupled with the designation of this virus as a global pandemic, it caused the biggest changes in stocks. The tourism and hospitality industry suffered the most due to the travel bans and lockdown. This examines stock market reaction on Pandemic COVID-19 by measuring the differences of stock prices and stock trading volumes in the South East-Asia capital market, namely the ASEAN Exchange for the period before and after the pandemic occurred. The sample used was 49 companies from the tourism and Hospitality sector included in the ASEAN Exchange. The data analysis technique used paired sample t-test and Wilcoxon signed rank test with quantitative data. The results found that the tourism and hospitality companies from Indonesia, Singapore and Thailand reacted to the Covid-19 pandemic.